Vote for Love: A Collection of Children's Sayings - Nanette Newman (UK Collins, 1976)
GB76-32912
ill. (some col.) ; compiled by Nanette Newman.
[34] p. : Byran Forbes Limited
Keywords: Theology: Miscellaneous; Children -- Quotations; Theology